One water-stable magnetic coordination polymer material (Fe3O4@PmPD–[Co-BT]) as an efficient adsorbent for rapid dye removal. (20th November 2020) - Wang, Lulu; Lu, Ziwen; Fan, Chuanbin; Zong, Ziao; Zhu, Bin; Bi, Caifeng; Zhang, Xia; Fan, Yuhua
Abstract : Benefiting from the framework, Fe3 O4 @PmPD–[Co-BT] has an excellent effect of removing CR from wastewater, and the adsorption capacity was 347.8 mg g −1 . Abstract : Recently, lots of organic dye adsorbents were introduced; the pollution of water bodies caused by adsorbents was an urgent problem to be solved. The modified metal–organic frameworks with magnetic properties provided a great platform for solving this disadvantage. In this study, a novel magnetic material Fe3 O4 @PmPD–[Co-BT] (Co-BT = [Co(bcpo)0.5 (tib)(H2 O)2 ] n, bcpo = 2, 5-bis(4-carboxylphenyl)-1, 3, 4-oxadiazole, tib = 1, 3, 5-tris(1-imidazolyl)benzene)) was prepared using Fe3 O4 modified by mPDs (mPD = m -phenylenediamine). This material was successfully characterized by transmission electron microscopy (TEM) and powder X-ray diffraction (PXRD), and it was confirmed that Co-BT was adhered to the Fe3 O4 surface by PmPDs. The dye adsorption performance of magnetic Fe3 O4 @PmPD–[Co-BT] was investigated in detail with selectivity, capacity, thermodynamics and kinetics studies, and with respect to influence factors including the pH value, solvent types, and ionic strength. Notably, the saturated adsorption capacity of magnetic Fe3 O4 @PmPD–[Co-BT] for CR dyes could reach 347.8 mg g −1 . The dye removal mechanism was investigated by zeta potential analyses and Fourier transform infrared (FTIR) spectroscopy.